Sensation Seeking, Deviant Peer Affiliation, and Internet Gaming Addiction Among Chinese Adolescents: The Moderating Effect of Parental Knowledge - Tian, Yunlong; Yu, Chengfu; Lin, Shuang; Lu, Junming; Liu, Yi; Zhang, Wei (Frontiers in Psychology, 2019)
Although there is abundant evidence that an association between sensation seeking and adolescent Internet gaming addiction (IGA) exists, research has provided little insight into why adolescents with high sensation seeking are more likely to be focused on Internet and video games. Grounded in the social development model and ecological systems theory, this study investigated whether deviant peer affiliation mediated the relationship between sensation seeking and adolescent IGA, and whether this indirect link was moderated by parental knowledge. Participants were 1293 Chinese adolescents (49.65% male, Mage = 12.89 ± 0.52 years) who completed questionnaires assessing sensation seeking, deviant peer affiliation, parental knowledge, and IGA. Structural equation models revealed that the positive association between sensation seeking and adolescent IGA was partially mediated by deviant peer affiliation. In addition, this indirect link was significantly moderated by parental knowledge. Specifically, the indirect path from sensation seeking to adolescent IGA was stronger for adolescents with low parental knowledge than for those with high parental knowledge. Identifying the role of peers and parents in the onset of adolescent IGA has key implications for prevention and intervention.